Efficacy and Safety in Combining Primary Palatoplasty and Myringotomy in Patients with Cleft Palate. Issue 5 (May 2020) - Mantilla-Rivas, Esperanza; Mamidi, Ishwarya; Rokni, Alex; Brennan, Ashleigh; Rana, Md Sohel; Goldrich, Agnes; Manrique, Monica; Shah, Monica; Reilly, Brian K.; Rogers, Gary F.; Oh, Albert K.
Abstract : Background: Patients born with a cleft lip and palate undergo multiple surgical procedures, increasing the infants' exposure to anesthesia and potential risk of neurocognitive delays. In addition, these numerous procedures lead to greater use of hospital resources. This study analyzes the differences in anesthetic exposure and perioperative characteristics between performing combined versus separate primary palatoplasty (PP) and placement of bilateral myringotomy tubes (BMT). Methods: We reviewed patients younger than 2 years who underwent PP and BMT at our institution from June 2014 to January 2019. Patients who underwent PP and BMT during the same admission (combined group = 74) and during separate admissions (separate group = 26) were studied. Due to the small sample size in the separate group, additional data for this group were gathered by propensity score matching by gender, race, and American Society of Anesthesiology class. Statistical analyses were carried out to identify significant differences between the 2 groups. Linear regression was performed to compare perioperative variables. Results: One hundred patients met the inclusion criteria. There were no significant differences in demographic characteristics or American Society of Anesthesiology class, surgery and anesthesia duration, dosage of intraoperative dexmedetomidine, hospital length of stay, and perioperative complications ( P > 0.05). Per contra, combined group had significantly lower intraoperative dosages of fentanyl ( P = 0.01) and shorter postoperative care unit stay ( P = 0.047). Conclusions: This study documents decreased postoperative care unit time and anesthesia drug exposure without increased length of stay or perioperative complications in patients undergoing combined PP and BMT. These results support combining PP and BMT to reduce exposure to potentially neurotoxic medications and to increase efficient utilization of hospital resources.